Sociodemographic determinants for risk exposure of child injuries at home with focus on burns - Strukčinskienė, Birutė; Strazdienė, Neringa; Bauer, Robert; Steiner, Monica (Social Welfare: Interdisciplinary Approach, 2019)
Burns are a significant public health problem that occurs at home and especially affect children. Non-fatal burn victims suffer from prolonged hospitalization, disfigurement and disability, with consequences of stigma and rejection. The survey on child injuries at home with focus on burns showed that sociodemographic determinants play an important role for child safety at home. The majority of home injuries were attributable to human and environmental factors. The main ways for prevention, including education, safe environment creation, legislation and enforcement can prevent child injuries (including burns or scalds) and promote safety at home, saving the lives of vulnerable age groups, especially children.